INDONESIAN TEACHER TEACHING STRATEGY IN LEARNING SPEAKING SKILLS OF MA MUHAMMADIYAH PALLEKO STUDENTS OF TAKALAR REGENCY - Dewi, Andi; Rahman Rahim, A; Muhammad Akhir (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to describe the teaching strategy of Indonesian teachers in learning speaking skills of MA Muhammadiyah Palleko students in Takalar Regency. The focus of the research is directed at the types of strategies used by teachers, their application in learning activities, and factors that affect the effectiveness of learning speaking skills. The research uses a qualitative approach with a descriptive method. Data is collected through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawn. The results of the study showed that teachers used several learning strategies, namely communicative strategies, group discussions, presentations, questions and answers, and role plays. The strategy is applied to increase students' speaking courage, ability to convey ideas, and their involvement in the learning process. However, the effectiveness of the strategy is still influenced by several obstacles, such as low student confidence, limited learning media, and suboptimal feedback by teachers. This study concludes that the teaching strategy of Indonesian teachers has been able to support the improvement of students' speaking skills, but still requires continuous innovation, especially in media development, strengthening motivation, and providing opportunities for wider speaking practice.